1964
DOI: 10.1152/ajplegacy.1964.207.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic separation of pepsins from human gastric juice

Abstract: Acid gastric juices have been fractionated on DEAE (diethylaminoethyl)-cellulose to yield three pepsin fractions, which have the same chromatographic mobility as the three pepsin fractions previously described in acidified whole gastric mucosal extracts. The acid gastric juices included specimens obtained from healthy individuals and from patients with peptic ulcer and gastritis. Gastric juice from one patient with pernicious anemia was shown to contain only pepsinogen I. A satisfactory chromatographic separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1968
1968
1983
1983

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Turner et al (1967) observed that the 4pepsin 1' of Seijffers et al (1964) was. stable at pH 70 and showed only a slow loss of activity between pH 7 0 and pH 7 5, whereas pepsins IIA, IIB, and III showed a rapid loss of proteolytic activity at pH 70.…”
mentioning
confidence: 99%
“…Turner et al (1967) observed that the 4pepsin 1' of Seijffers et al (1964) was. stable at pH 70 and showed only a slow loss of activity between pH 7 0 and pH 7 5, whereas pepsins IIA, IIB, and III showed a rapid loss of proteolytic activity at pH 70.…”
mentioning
confidence: 99%
“…0.1 M acetate buffer (pH 5 3) was made from 0-1 M sodium acetate and 0.1 M acetic acid. Appropriate amounts of sodium chloride, as described below, were added for gradientelution chromatography (Seijffers et al, 1964).…”
Section: Methodsmentioning
confidence: 99%
“…DiscussionThe chromatographic technique gave reasonably reproducible results(Seijffers et al, 1964) but temperature control was critical to obtain satisfactory separation of the three pepsin fractions. However, even with satisfactory chromatograms it was not possible to determine the proportions…”
mentioning
confidence: 88%
See 2 more Smart Citations